Design and characterization of planar antennas on the semi-insulated GaAs for rectenna devices - Mustafa, Farahiyah; Rusli, Nurul Izni; Hashim, Abdul Manaf (2008)
This paper presents the design and characterization of the planar type antennas. A dipole type antenna has been designed to be used in the rectifying antenna (rectenna) devices. Normally, a rectenna consists of an antenna and a diode which can rectify microwave power to dc power. We present the novel coplanar waveguide (CPW) facilitated with antenna for future applications such as Intelligent Quantum (IQ) Chips. The return loss characteristic of antenna has been investigated by simulation. From our preliminary results, it is shown that an antenna with length, L=4mm and width, W=20Î¼m showed high return loss characteristics up to -47dB at 15GHz. The obtain characteristics also showed that the dipole antenna can be directly integrated with other devices without any matching circuits for use like in approximity communication system.